An overview of Urban Flooding in Dibrugarh Town, Assam - Suntoo Das,Uttam Mili,Prasanna Bora (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Urban flood is very common in most of the Indian cities. Unplanned urbanization is primarily responsible for urban flood in India. The rate of urbanization in India has been increasing rapidly. According to 1901 census, 11.4% of the total population was residing in urban areas. This count has been increased by 28.53% in 2001 and 31.16% in 2011. This rapid urbanization leads to many problems in urban areas because it is happening without any proper planning. One of such problem is causing urban flood. Unplanned urbanization comes up with an improper urban drainage system, illegal construction of buildings in low lying areas, construction of buildings without acknowledging the natural topography and hydro-geomorphology etc. All these factors combined with excessive rainfall causing urban flood within a very short period of time. Dibrugarh is one of the largest and important cities of upper Assam where urban flood also occurs mainly during the summer season (Jun-Sept). It creates havoc among the city dwellers. Through this paper, the author simply highlights the urban flood events in Dibrugarh, their occurrences and consequences.